Quality of Early Childhood Education and Care in Kazakhstan: The First Nationwide Study - Kiikova, Gaukhar; Bektemirova, Altynay; Ramazanova, Aizhan; IssinaZhazira; Chukurova, Sogdiana (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
Currently, Kazakhstan has the highest enrolment rate in the history of early childhood education and care (ECEC), with 98% enrolment for children aged three to six years old. With this significant expansion of ECEC, there is a lack of sufficient evidence on its overall quality. This study is the first countrywide study aimed to evaluate the ECEC quality in Kazakhstan using the internationally recognized Early Childhood Environment Rating Scale (ECERS-3). We looked at 50 preschool classrooms from all regions of Kazakhstan. The preschools had different combinations of the following characteristics: located in urban/rural areas; state/private; with Russian/Kazakh-language instruction. The scores demonstrated ‘below the minimal’ quality of ECEC in Kazakhstan. No correlation was found between the quality of ECEC and regions or types of settlement. Findings revealed such problems as deprivation of play, predominance of teacher-led pedagogy, large child-to-staff ratio and others. Children are not offered adequate amounts or variety of cognitively stimulating opportunities that would support their development and learning. There was a statistically significant difference in quality depending on the language of instruction. Kazakh groups were more likely to score worse than Russian ones (N=47, p=.026). The reasons for these findings are numerous, both due to the complexity of the ‘quality’ notion, as well as various issues that influence the quality of ECEC in Kazakhstan.